Peru : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper for Peru explains growth and reform in the country post-1990. As half of the population in Peru still lives below the poverty line, further research should consider how the link between average income improvements and poverty reduction can be strengthened. Although the ongoing decentralization effort in Peru has been based on considerations of fiscal sustainability, more work needs to be done to ensure that the conditions for a successful decentralization are in place. The experience of Peru teaches that sound macroeconomic policies are a precondition for de-dollarization.